A midline pelvic mass: Ovarian fibroma appearing vaginal in nature. (February 2023) - Li, Michael C; Polk, Stuart L; Myers, Ross A
Introduction: Ovarian fibroma is an uncommon, benign, stromal neoplasm that is a mixture of collagen-producing mesenchymal cells. There are varying sonographic and computed tomography features described in literature of smaller scale studies. Case Report: We describe a case of an ovarian fibroma presenting as a midline pelvic mass mimicking a vaginal cuff tumour in a 67-year-old patient with surgical history of a hysterectomy. Computed tomography and ultrasound were utilised to evaluate the mass and guide management of the patient. The mass was initially suspected on CT-guided biopsy as a vaginal spindle cell epithelioma amongst other potential differential considerations. With robot-assisted laparoscopic surgery and histologic analysis, the true diagnosis of an ovarian fibroma was reached. Discussion: An ovarian fibroma is an uncommon, benign, stromal ovarian tumour, representing just 1-4% of all ovarian tumours. Its widely varying imaging features present a challenge when radiologically evaluating ovarian fibromas or pelvic tumours, as the differential diagnoses are extensive and ovarian fibromas are often misdiagnosed until surgical resection. We highlight the features of ovarian fibromas and the potential value of pelvic/transvaginal ultrasonography in management of ovarian fibroma and other pelvic masses. Conclusion: The use of computed tomography and ultrasound aided in the diagnostic and treatment pathway of this patient with a pelvic mass. There is high utility of sonography in evaluating such tumours to elucidate salient features, expedite diagnosis, and guide further management.